Changing lung function and associated health-related quality-of-life: A five-year cohort study of Malawian adults. (November 2021) - Njoroge, Martin W.; Mjojo, Patrick; Chirwa, Catherine; Rylance, Sarah; Nightingale, Rebecca; Gordon, Stephen B.; Mortimer, Kevin; Burney, Peter; Balmes, John; Rylance, Jamie; Obasi, Angela; Niessen, Louis W.; et al.
Abstract: Background: In Sub-Saharan Africa cross-sectional studies report a high prevalence of abnormal lung function indicative of chronic respiratory disease. The natural history and health impact of this abnormal lung function in low-and middle-income countries is largely unknown. Methods: A cohort of 1481 adults representative of rural Chikwawa in Malawi were recruited in 2014 and followed-up in 2019. Respiratory symptoms and health-related quality of life (HRQoL) were quantified. Lung function was measured by spirometry. Findings: 1232 (83%) adults participated; spirometry was available for 1082 (73%). Mean (SD) age 49.5 (17.0) years, 278(23%) had ever smoked, and 724 (59%) were women. Forced expiratory volume in one second (FEV1 ) declined by 53.4 ml/year (95% CI: 49.0, 57.8) and forced vital capacity (FVC) by 45.2 ml/year (95% CI: 39.2, 50.5) . Chronic airflow obstruction increased from 9.5% (7.6, 11.6%) in 2014 to 17.5% (15.3, 19.9%) in 2019. There was no change in diagnosed asthma or in spirometry consistent with asthma or restriction. Rate of FEV1 decline was not associated with diagnosed Chronic obstructive pulmonary disease (COPD), asthma, or spirometry consistent with asthma, COPD, or restriction. HRQoL was adversely associated with respiratory symptoms (dyspnoea, wheeze, cough), previous tuberculosis, declining FEV1 and spirometry consistent with asthma or restriction. These differences exceeded the minimally important difference. Interpretation: In this cohort, the increasing prevalence of COPD is associated with the high rate of FEV1 decline and lung function deficits present before recruitment. Respiratory symptoms and sub-optimal lung function are independently associated with reduced HRQoL. Funding: This was funded by a New Investigator Research Grant from the Medical Research Council (Ref: MR/L002515/1), a joint Global Health Trials Grant from the Medical Research Council, UK Department for International Development and Wellcome Trust (Ref: MR/K006533/1, a US National Institutes for Health R56 Grant (Ref: R56ES023566) and by the National Institute for Health Research (NIHR) (project reference 16/136/35) using UK aid from the UK Government to support global health research.